النزعة الدينية في ديوان "أحدث الليل" لمحمد المقرن: دراسة تحليلية: (Religious Tendency in the Collection of ‘Aḥdath al-Layl’ (The Latest Night) by Muhammad Al-Muqrin: An Analytical Study) - نورة حميد حمدي الكبكبي (At-Tajdid - Intellectual Refereed Journal, 2024)
This research examines contemporary poetic creativity through the collection of poems by the poet Muhammad Al-Muqrin, titled "The Latest Night". The study delves into the poetic details and analyzes the emotional experiences connected to the religious inclination in expressions, visions, ideas, imaginations, styles, and structures. The aim is to shed light on Muhammad Al-Muqrin’s experiences in light of his religious inclination and Islamic identity, and how the poet managed to blend this identity with poetic creativity. The research addresses a specific issue: how religious upbringing and Islamic background influence the poet’s direction, giving his poetry a clear inclination. The researcher structured this study into two main sections, preceded by an introduction and preamble, and followed by a conclusion. Such literary studies focus on the analytical aspect of highlighting artistic values, analyzing poetic models, and linking all this to the religious identity and Islamic inclination that are prominently featured in the collection’s internal details. The study primarily adopts an analytical method, with reliance on historical, deductive, and descriptive methods. The research reached many conclusions, the most significant of which is that religion has a significant impact on poets’ experiences; it clearly affects their style, language, thought, and poetic imagery. This phenomenon is evident among many poets across different literary periods. In modern times, religion has had a strong presence in countless poetic texts, indicating that poets are influenced by their religious identity and intellectual affiliations. Muhammad Al-Muqrin lived in a conservative environment that adhered to religious teachings, fulfilled its duties, and worked on spreading values and virtues among its members. This environment had a clear and tangible influence on his experiences and poems in his collection "The Latest Night". Keywords: "The Latest Night" collection, religious inclination, Muhammad Al-Muqrin.